Indonesian Public Response to Online Learnings During the Covid-19 Pandemic: An Analysis of Social Media - Prabowo, Thoriq Tri; Suroso, Dwi Joko (Indonesian Journal of Teaching in Science, 2022)
Online Learnings that were implemented during the Covid-19 pandemic invited pros and cons, especially on social media, that could be directly observed by the public. When analyzed properly, the pros and cons contain valuable information that the authorities can use to evaluate Online Learning policies. This study describes the narrative developed on social media Twitter related to Online Learning during the Covid-19 pandemic. This research includes the social network analysis (SNA) research with a descriptive qualitative approach. The platform used to collect data is Drone Emprit Academic (DEA), an SNA tool. The data analyzed relates to the number of tweets, influential actors, narrative sentiments, and robots that tweet the topic. This research does not contribute justification for right and wrong but attempts to present reliable data exposure. Based on Online Learning tweets collected on July 22-29, 2020, there were 2,903 tweets. The tweets are classified as organic because the influential actors come from personal accounts, not accounts of famous figures. Criticism of Online Learning administration is the dominant response because there is still an economic and digital divide among the public. The government needs to evaluate Online Learning policies and reconsider just education during the Covid-19 pandemic.